The Ford Resource and Engagement Centre (FREC) programme's contribution to mitigate poverty : perspectives from participants - Claassens, Elmien (University of Pretoria, 2024)
Mini Dissertation (MSW (Social Development and Policy))--University of Pretoria, 2023.